Arabic Miniatures - Political Miniatures of Sicily as a Model - Oklah, Dr.Manal Hassan (Thi Qar Arts Journal, 2024)
Miniatures are illustrative drawings that appeared in a variety of manuscripts. Their purpose was to facilitate the understanding of written texts or to clarify them in the form of a pictorial artwork. They initially flourished in the Islamic world during the period of conquests. As the Islamic conquests progressed, they encountered European countries, especially those ruled by Arab Muslims, including Sicily, which was ruled by the Fatimids (297 AH-484 AH / 910-1091 AD). The Fatimids ruled Sicily through their governors, the Kalbids and others, for two centuries after establishing a large fleet aimed at protecting the country from Byzantine attacks and later defending it during the Crusades. Their goal was also to spread the Ismaili doctrine and achieve many of their ambitions in a short period. During that period, governors ruled Sicily on behalf of the Fatimids, marking the era of the governors (296-336 AH / 908-947 AD), followed by the rule of the Kalbid princes in the name of the Fatimid state (Hamawi, 1995, p. 392) (Idrisi, 1989, p. 762).The Arab artist in Sicily was distinguished by his unique touch in this art, which led to its flourishing in other countries. Despite the simplicity of the style that characterized the art of miniatures at the beginning, it developed over time and became characterized by realism and expressiveness. It is an art that calls for drawing inspiration from the past and reviving it.Political miniatures are considered one of the important topics highlighted in this research due to their historical significance. Political-themed miniatures were regarded as documents relied upon in historical and political references and others.